220k views
5 votes
Thomas is doing a proof for solving the equation 6(2x-5)=-34

2 Answers

5 votes

Explanation:

  • 6(2x-5)=-34
  • 12x-30=-34
  • 12x=-34+30
  • 12x=-4
  • x=-4/12
  • x=-0.333
User Will M
by
6.3k points
3 votes

Answer: x = -1 / 3

Explanation:

Given expression

6 (2x - 5) = -34

Expand the parentheses and apply the distributive property

6 · 2x - 6 · 5 = -34

12x - 30 = -34

Add 30 on both sides

12x - 30 + 30 = -34 + 30

12x = -4

Divide 12 on both sides

12x / 12 = -4 / 12


\boxed{x=-(1)/(3) }

Hope this helps!! :)

Please let me know if you have any questions